Pengaruh Perbandingan Konsentrasi Rumput Laut Terhadap Total Bakteri dan Ragi Kombucha (Kappaphycus Alvarezii) Selama Proses Produksi - Rikky Leonard Rikky; Dwitha Nirmala; Rahayu Kusdarwati; Pamela (Airlangga University, 2023)
The comparison of the concentration of Kappaphycus alvarezii seaweed is estimated to affect the total bacteria and yeast during the kombucha production process. The carbohydrate content in seaweed can be one of the factors for the formation of nata as a parameter for the success of making kombucha, as well as its effect on nutrition for bacterial and yeast growth. This study aims to determine the effect of comparing the concentration of seaweed on the total bacteria and yeast kombucha Kappaphycus alvarezii. The method used in this study is an experimental method with a completely randomized design (CRD) with six treatments and 4 replications. The results of this study indicate that the comparison of the concentration of Kappaphycus alvarezii seaweed affects the total bacteria and yeast during the kombucha making process. The total bacteria test showed that the total bacteria increased until the 3rd day and the highest total yield was found in the control treatment, which was 1,6x107 CFU/ml on the 3rd day. Then the total yeast also increased until the 3rd day and the highest yield was found in the control treatment of 2,3x107 CFU/ml.